Evaluation and Comparison of Manual and Mechanical Endodontic Instrumentation Completed by Undergraduate Dental Students on Endodontic Blocks - António Ginjeira; Abayomi O. Baruwa; Karla Baumotte (Dentistry Journal)
Background: The shaping of root canal space was completed using manual stainless steel files in earlier decades and with the advent of mechanical nickel–titanium (NiTi) instruments, there is potential for more efficient root canal preparation. Despite the advantages of NiTi instruments, their adoption in undergraduate dental education remains limited. The aim of this study was to evaluate three root canal instrumentation techniques, manual instrumentation using stainless steel hand files, continuous rotation employing ProTaper Gold (PTG) files, and reciprocation with WaveOne Gold (WOG) files, on endodontic resin blocks to assess the quality of preparation and the time required for instrumentation. Methods: A total of 36 third-year dental students, all lacking prior experience in root canal procedures, were divided into six groups to prepare 108 resin endodontic blocks with each student preparing 3 blocks. Images were captured at the preoperative, intraoperative, and postoperative stages to facilitate comparisons and measurements of the prepared blocks to assess the degree of resin removal, apical deviation, and mid-cervical wear. Furthermore, questionnaires were distributed to assess the students’ experiences and satisfaction with the techniques. The Friedman test, Wilcoxon test with Bonferroni correction, and Kruskal–Wallis test with Mann–Whitney U test were used to analyse and compare techniques, with the level of significance set at p < 0.05. Results: Instrumentation with PTG exhibited significantly reduced apical deviation (0.073 ± 0.003) compared to both the WOG and manual instrumentations (p < 0.001). Significant differences in mid-cervical wear were observed only between PTG and the manual instrumentation. In terms of resin removal, the manual instrumentation displayed greater variability and was five times slower to complete the instrumentation. In total, 90% of students favoured mechanical instrumentation, with substantial preferences for them over manual techniques. Conclusions: Mechanical instrumentation techniques, notably with the PTG system, were significantly faster and more effective in preparation quality. This highlights the potential for the inclusion of mechanical instrumentation in undergraduate dental curricula.